Üniversite Öğrencilerinin Üniversiteye Uyum ve Psikolojik Yardım Aramaya İlişkin Görüşleri - Müezzin, Ece Emre; Kaya, Alim (İstanbul Kültür Üniversitesi / Eğitim Fakültesi, 2018)
Bu araştırmada Kuzey Kıbrıs Türk Cumhuriyeti’nde eğitim gören KKTC’li ve T.C.’li üniversite öğrencilerinin üniversiteye uyum ve psikolojik yardım aramaya ilişkin görüşleri incelenmiştir. Nitel araştırma desenlerinden durum çalışması olarak gerçekleştirilen bu araştırmada, çalışma grubu 16’sÍ (8 kadın, 8 erkek) T.C. uyruklu ve 16’sÍ(8 kadın, 8 erkek) KKTC uyruklu lisans öğrencisinden oluşmaktadır. Dört farklı görüşme formu kullanılan araştırmada, öğrencilerin üniversiteye gelme kararları, üniversitede yaşamış oldukları uyum sorunları, uyum sorunlarıyla baş etme stratejileri, ailelerinin yanında veya ayrı eğitim almaları, üniversiteye aidiyet duyguları ve psikolojik yardım aramaları ile ilgili görüşleri alınmıştır. Görüşmelerden elde edilen veriler üzerinde betimsel analiz yapılmıştır. Araştırmanın sonucunda kendi ailelerinin yanında eğitim alan KKTC’li öğrencilerin ailesinden ayrı eğitim alan T.C.’li öğrencilere göre ailesinden çok kendi kararı ile bulunduğu üniversitede eğitim aldığı sonucuna varılmıştır. KKTC’li öğrencilerin daha çok arkadaş edinmek T.C.’li öğrencilerin ise ailelerinden ayrı kalmış olmak gibi uyum sıkıntılarının olduğu anlaşılmıştır. KKTC’li ve T.C.’li öğrencilerin uyum sıkıntıları ile ilgili baş etme stratejisi olarak ailelerinden destek aldıkları sonucu çıkarılmıştır. KKTC’li öğrencilerin çoğu ailelerinin yanında eğitim almaktan memnun olduklarını belirtirken T.C.’li öğrencilerin ailelerinden ayrı eğitim aldıkları için memnun oldukları sonucuna varılmıştır. KKTC’li ve T.C.’li öğrencilerin büyük bir çoğunluğunun eğitim alınan üniversiteye kendilerini ait hissettikleri sonucu ortaya konmuştur.

The purpose of this research is to study the attitudes of students who come from Turkey and the Turkish Republic of Northern Cyprus (TRNC), towards seeking professional psychological counselling and their psychological adaptation at their university in the TRNC. This study was conducted as a case study using a qualitative research design. The study group was made up of 16 students who were citizens of Turkey (8 females, 8 males) and 16 students were the citizens of the TRNC (8 males, 8 females). Four interview forms were used in this research; interview sessions with the students focused on their decisions about attending their present university as well as the problems of adaptation they faced, the strategies they used in dealing with adaptation, getting education while staying with their families or away from their families, feelings of belonging they have to their universities and their attitudes on getting psychological counselling. The findings have been descriptively analysed. The conclusion reached from the findings of this research indicated that the decision to study at their present university was a personal decision for students coming from the TRNC who lived with their families whereas for students who came from Turkey the decision was made by their families. The findings also indicate that students from both the TRNC and Turkey tend to seek counselling from their families as the prominent coping strategy on issues of adaptation. Students from the TRNC expressed their satisfaction of staying with their families and students from Turkey expressed their satisfaction of attending a university away from their families. The findings also indicated that students felt themselves belonged to the university they were getting education in. Keywords: ochesion, attitude on seeking for psychological help, university student.
The University Students’ Opinions to Adaptation to the University and Seeking Professional Psychological Counselling
Keywords: Uyum; Psikolojik Yardım Arama Tutumu; Üniversite Öğrencisi; Ochesion; Attitude on Seeking for Psychological Help; University Student